Mechanistic Study of Macranthoside B Effects on Apoptotic Cell Death in Human Cervical Adenocarcinoma Cells - Li, Y; Li, M; Ahmed, K; Yang, J; Song, L; Cui, Z. G; Hiraku, Y (Folia biologica, 2022)
Macranthoside B (MB) is a triterpenoid saponin extracted from Lonicera macranthoides, a traditional Chinese medicine. In the current study, we investigated the anticancer potential of MB in various cancer cells and elucidated its underlying mechanisms. MB exposure inhibited cell proliferation, induced mitochondrial membrane potential (MMP) loss, increased sub-G1 accumulation, and resulted in cleavage of caspase-3 and PARP, which are reflective of apoptosis. In HeLa cells, MB induced down-regulation of SOD2 and GPx1, phosphorylation of Akt and PDK1, and thus promoted ROS-mediated apoptosis. This was further supported by the protection of sub-G1 accumulation, MMP loss, cleavage of caspase-3 and PARP in the presence of N-acetylcysteine (NAC). Additionally, MB induced cell death via down-regulation of ubiquitin-like with PHD and ringfinger domains 1 (UHRF1) and Bcl-xL. Taken together, this study provides a new insight into the apoptosis- inducing potential of MB, and its molecular mechanisms are associated with an increase in oxidative stress and inhibition of the PDK1/Akt pathway.
Keywords: Saponins; Poly(ADP-ribose) Polymerase Inhibitors; Caspase 3; nádorové buněčné linie; Cell Line, Tumor; Humans; Ubiquitin-Protein Ligases; proteiny vázající zesilovač transkripce CCAAT; Membrane Potential, Mitochondrial; Reactive Oxygen Species; HeLa Cells; apoptóza; HeLa buňky; kaspasa 3; saponiny; membránový potenciál mitochondrií; PARP inhibitory; Adenocarcinoma; CCAAT-Enhancer-Binding Proteins; adenokarcinom; lidé; reaktivní formy kyslíku; Apoptosis; ubikvitinligasy; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt